A Liquid Crystalline Phase with Uniform Tilt, Local Polar Order and Capability of Symmetry Breaking. (20th February 2013) - Alaasar, Mohamed; Prehm, Marko; Nagaraj, Mamatha; Vij, Jagdish K.; Tschierske, Carsten
<x xml:space="preserve">Abstract</x> A new liquid crystalline (LC) phase with uniform tilt, local polar order and capability of symmetry breaking is found for a bent‐core mesogen combining a 4‐cyanoresorcinol unit with two azobenzene wings. The combination of local polar order and long range synclinic tilt in this SmCsPR phase leads, under special conditions, to macroscopic domains with opposite chirality, though the molecules themselves are achiral. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>